2016
DOI: 10.1108/ijebr-07-2014-0135
|View full text |Cite
|
Sign up to set email alerts
|

From “great expectations” to “hard times”

Abstract: This document may differ from the final, published version of the research and has been made available online in accordance with publisher policies. To read and/or cite from the published version of the research, please visit the publisher's website (a subscription may be required.) Approach: Seven digital creative nascent graduate entrepreneurs were followed for up to five years. Although independently assessed as having promise of business success, they were young and lacked business experience. They were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Due to a lack of EM skills, graduate entrepreneurs are struggling in their ventures, particularly during the startup phase, which is causing them to experience entrepreneurial failure (Hanage et al, 2016). Business schools worldwide are teaching EM in the way they teach traditional entrepreneurship or marketing courses (i-e., traditional coursework), whereas, the researchers of entrepreneurship education argue that entrepreneurship courses should be designed and delivered with the "practically oriented" content and teaching pedagogy in mind because practically oriented courses significantly develop skills that affect highly on practical entrepreneurial outputs (Piperopoulos & Dimov, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a lack of EM skills, graduate entrepreneurs are struggling in their ventures, particularly during the startup phase, which is causing them to experience entrepreneurial failure (Hanage et al, 2016). Business schools worldwide are teaching EM in the way they teach traditional entrepreneurship or marketing courses (i-e., traditional coursework), whereas, the researchers of entrepreneurship education argue that entrepreneurship courses should be designed and delivered with the "practically oriented" content and teaching pedagogy in mind because practically oriented courses significantly develop skills that affect highly on practical entrepreneurial outputs (Piperopoulos & Dimov, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Standard marketing in textbooks was originally developed for larger enterprises, and it widely ignores the marketing particularities of SMEs (Grünhagen & Mishra, 2008;Kraus et al, 2007). A study on digital creative graduate entrepreneurs in the UK, have found the nascent entrepreneurs unprepared for entering a competitive marketplace due to lack of marketing skills, insufficient professional experience, and weak selling skills (Hanage et al, 2016), which indicates a wide theory-practice gap in EM. Many other researches on EM also show a clear theory-practice gap in the area and argue that SMEs often have different marketing behavior than that from the classic textbook approaches and the way these are taught in the business schools (Hills et al, 2010;Maritz et al, 2010;Resnick et al, 2011;Resnick et al, 2016).…”
Section: Entrepreneurial Marketing Theory and Practicementioning
confidence: 99%
“…Thus, higher education institutions (HEIs) could play a vital role for the development of sustainable https://doi.org/10.1016/j.ijme.2020.100379 Received 24 September 2019; Received in revised form 20 January 2020; Accepted 17 February 2020 entrepreneurship in the economies (Franco, Haase, & Lautenschlager, 2010;Klapper, 2014;Libombo & Dinis, 2015;Ncanywa, 2019). HEIs worldwide have recently recognised this role (Manimala, 2017), however, they still lag behind in making suitable pedagogical developments within EE as compared to the practical entrepreneurial needs (Alabduljader, Ramani, & Solomon, 2018;Bakhtiari, 2017;Hanage, Scott, & Davies, 2016;Iwu et al, 2019). This contemporary issue of mismatched pedagogical approaches in EE with practical entrepreneurial needs is also causing graduate entrepreneurial failure (Agostini, 2016;Cant & Wiid, 2017;Garo, 2017;Gummesson, 2014;Hutt & Walker, 2015;Molin & Sjöberg, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The failure of nascent entrepreneurs not only affects the failing entrepreneurs but also demoralizes upcoming graduates for choosing the entrepreneurial careers (Bakhtiari, 2017). In such a challenging and risky environment, even if the graduates take the initiative to start their ventures, Hanage et al (2016) have found such graduate entrepreneurs underprepared to perform marketing functions during the start-up phase of their small or medium-sized enterprises (SMEs).…”
Section: Introductionmentioning
confidence: 99%